Yoga Exercise Intervention Improves Balance Control and Prevents Falls in Seniors Aged 65 - Krejčí, Milada; Hill, Martin; Kajzar, Jiří; Tichý, Miroslav; Hošek, Vaclav (Zdravstveno varstvo, 2022)
INTRODUCTION: Body balance control represents a key factor preventing falls and subsequent injuries in seniors aged 65+. Intervention based on yoga exercises seem to be effective in improving balance. OBJECTIVE: The objective is to analyse and compare changes in static, dynamic, and total balance scores, changes in body composition and social indices as effects of yoga-based intervention. METHODS: A total of 500 participants (234 men aged 74.5 SD±7.74 and 266 women aged 76.9 SD±7.23) were assessed using the Tinetti Balance Assessment Tool, the InBody 230 bioimpedance body composition analyser, and the SF-36 Health Survey, applied to pre and post-testing. The experimental group (n=262; 122 males; 140 females) underwent a four-week yoga-based intervention, 30 minutes daily, while the control group (n=238; 112 males; 126 females) underwent its usual daily programme at senior homes or centres. The ANOVA model, consisting of the Group, Stage, Subject and Group × Stage interaction factors, was used for data evaluation. RESULTS: Intervention led to improvements in the static, dynamic and total balance scores in the experimental group compared to the control group. The results of SF-36 showed positive changes in the psychosocial aspects of health, such as promoting of calmness and happiness in male seniors and reducing fatigue, nervousness and depression in female seniors. The post-intervention decrease in body fat percentage and increase in muscle mass in seniors is discussed. CONCLUSIONS: The four-week yoga-based intervention had positive effects on the static, dynamic and total balance scores, body composition and social status.
Keywords: social health; chair yoga; balance control; ageing; health promotion